Review of the book Geography: a weapon for war, 1976 - Herrera Rodríguez, Leonardo Fabrizio (2021)
The author maintains that there is a total lack of interest in spatial analysis on the part of societies, and that the set of geographic knowledge is only used by those who hold power. Said laziness about geographic issues is mainly due to school geography and spectacle geography, which dress geographic science with a contemplative, passive and disinterested cloak, or, better said, uselessness. To these factors, daily and academic activities are added, which together move us away from the definition that knowledge related to space is a powerful instrument to wage war and to exercise power.